2022
DOI: 10.1002/mds.29204
|View full text |Cite
|
Sign up to set email alerts
|

The Sphingolipids Clearly Play a Role in Parkinson's Disease, but Nature Has Made it Complicated

Abstract: A recent article in this journal 1 adds to a growing avalanche of data concerning the relationship between sphingolipid metabolism and Parkinson's disease (PD). The focus on this connection owes to the fact that mutations in the GBA1 gene have been linked to the risk and the rate of progression of PD (GBA1 is one of a very few genes that are related to both 2,3 ). GBA1 encodes the lysosomal enzyme glucocerebrosidase (GCase), which catalyzes the hydrolysis of the sphingolipid glucosylceramide (GluCer) to produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Over the last several years, there has been an increasing appreciation for the role that gangliosides and sphingolipids in general may play in the pathogenesis and progression of neurodegenerative diseases ( Maglione et al, 2010 ; Di Pardo and Maglione, 2018 ; Lansbury, 2022 ) and PD in particular ( Chiricozzi et al, 2020 ; Ledeen et al, 2022 ; Schneider, 2022 ). However, less attention has been paid to the roles that possible alterations in expression of genes involved in glycosylation, sialylation, and S1P regulation may play in the development and progression of PD.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last several years, there has been an increasing appreciation for the role that gangliosides and sphingolipids in general may play in the pathogenesis and progression of neurodegenerative diseases ( Maglione et al, 2010 ; Di Pardo and Maglione, 2018 ; Lansbury, 2022 ) and PD in particular ( Chiricozzi et al, 2020 ; Ledeen et al, 2022 ; Schneider, 2022 ). However, less attention has been paid to the roles that possible alterations in expression of genes involved in glycosylation, sialylation, and S1P regulation may play in the development and progression of PD.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with PD, GCase deficiency specific to the SN was reported, 34 but in either putamen or cerebellum of patients with PD with or without GBA mutation(s), there were no or few changes in glucosylsphingosine, sphingomyelin, gangliosides (GM2, GM3), or total cholesterol. 8,39,40 In fact, other studies even reported reduced glycosphingolipids in brain regions with significant PD pathology (discussed in Lansbury 17 ) and compensatory upregulation of ceramide synthase-1 gene expression, 30 which would possibly increase overall sphingolipid recycling per time (flux). In PD, multiple glycosphingolipid abnormalities were observed in plasma independent of changes in GlcCer or GCase.…”
Section: Discussionmentioning
confidence: 99%
“…41 Thus, GlcCer in brain or plasma appears not to be the most appropriate reporter for shifts in lipid homeostasis. 17 Considering these aspects and the fact that the loss of one GBA allele in GBA-PD is not expected to result in significant GlcCer accumulation, it has been questioned whether GCS inhibition is in fact a valid approach to treat PD. 17 To add to this complexity, our data support the general notion in the field that sphingolipid composition may differ between brain regions and throughout disease progression and, therefore, that global GCS inhibition may possibly be benign for some neuronal circuits affected by disease, but not for others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in one GBA -PD cohort mild increases in levels of Cer, hexosylceramide (GlcCer and GalCer) and LacCer were observed in serum samples ( Guedes et al, 2017 ). The lack of compelling evidence may be due to the nature of the samples that were studied or the dynamic flux in SLs ( Lansbury, 2022 ). However, a role for SLs in the progression of PD is supported by studies in animal models, mostly in fruit flies.…”
Section: Parkinson’s Disease and Parkinsonismmentioning
confidence: 99%